Perencanaan Keuangan Keluarga untuk Anggota BKM Unggul Jaya Pecangaan Kulon, Jepara - Faiqul Hazmi; Ahmad Fauzan Mubarok (Universitas Mathla'ul Anwar Banten, 2019)
FAMILY FINANCIAL PLANNING FOR MEMBERS OF BKM UNGGUL JAYA PECANGAAN KULON, JEPARA. Community Self-Reliance Agency of Unggul Jaya (BKM) is as a local non-profit institution. The members are the citizen of Pecangaan Kulon. The management and the staff are grouped voluntarily. The program of the community self-reliance agency is financial services for micro business group. The positive impacts of the program are (1) increasing community welfare; (2) increasing job opportunities from villagers. However, social dynamics leave problems such as the diversion of loan objectives is not in accordance with the average business application of businesses to non-businesses such as school funding, household purchases, house improvement, jewelry, entertainment, etc. It causes negative impacts such as (1) additional debt for members; (2) the changing of food consumption to debt payments; (3) bad loans so that funds cannot be handed over to other members; (4) the increased debt of the member to other institutions so that it makes getting worse for the finance; (5) the conflict of payment in a group; (6) the environmental development programs have stalled due to insufficient funding participation because members do not have good financial planning; (7) the environmental services and finance programs will be terminated by BKM to the environment which has arrears in installments. The solutions provided in the service program are (1) providing skills in determining the priority scale of household needs; (2) providing financial planning skills; (3) providing Financial Check-Up training; (4) providing skills in making a family financial budget; (5) Assisting and monitoring participants.